Soft X‐ray induced radiation damage in thin freeze‐dried brain samples studied by FTIR microscopy. (21st August 2020) - Surowka, Artur D.; Gianoncelli, A.; Birarda, G.; Sala, S.; Cefarin, N.; Matruglio, A.; Szczerbowska-Boruchowska, M.; Ziomber-Lisiak, A.; Vaccari, L.
Abstract : Soft X‐ray‐induced radiation damage was studied by FTIR microscopy in thin freeze‐dried brain tissue samples mounted onto Si3 N4 membrane windows. In addition to degradation of molecular assemblies in the tissue, the irradiation was discovered to induce detectable and reversible Si protonation in the Si3 N4 substrate, not visible in polymeric model samples. Abstract : In order to push the spatial resolution limits to the nanoscale, synchrotron‐based soft X‐ray microscopy (XRM) experiments require higher radiation doses to be delivered to materials. Nevertheless, the associated radiation damage impacts on the integrity of delicate biological samples. Herein, the extent of soft X‐ray radiation damage in popular thin freeze‐dried brain tissue samples mounted onto Si3 N4 membranes, as highlighted by Fourier transform infrared microscopy (FTIR), is reported. The freeze‐dried tissue samples were found to be affected by general degradation of the vibrational architecture, though these effects were weaker than those observed in paraffin‐embedded and hydrated systems reported in the literature. In addition, weak, reversible and specific features of the tissue–Si3 N4 interaction could be identified for the first time upon routine soft X‐ray exposures, further highlighting the complex interplay between the biological sample, its preparation protocol and X‐ray probe.